Ohranjanje gozdnih genskih virov s semenarskim praktikumom - Kraigher, Hojka (University of Maribor Press, 2024)
Conservation of Forest Genetic Resources With Seed Practicum. The textbook is intended for students and professionals in the field of conservation of biotic diversity with an emphasis on the conservation of genetic diversity, silviculturers and forest seed dealers and responsible in forest nurseries. It includes the basics of forest genetics, presents the importance and theoretical basis for the conservation of forest genetic resources, the Strategy for conservation of forest genetic resources in Europe, EUFORGEN and SIFORGEN programs (Slovenian program for the conservation of forest genetic resources). Botanical rpesentations of seed structure and germination physiology. Technologies of collection, processing and storage, and germination of seeds of forest tree species. Basics of seedlings production in forest nurseries. European and Slovenian legislation in the field of forest reproductive material. Examples of documents used in the approval of forest seed objects (basic material) and certification of forest reproductive material.